EVALUASI PENGENDALIAN INTERNAL BARANG JAMINAN GADAI PADA PT. PEGADAIAN PERSERO CABANG MALALAYANG - Aumaila, Vallen; Sondakh, Jullie J.; Pinatik, Sherly (Universitas Sam Ratulangi, 2018)
As the times progressed, development in every country is very rapid. This is seen from the level of development of science and technology, social, and political. All the countries of the world race to use all the skills and knowledge they have to fit the development. Similarly, in order to support the national development program, various government and private institutions participate in various efforts to support the development of the nation. With the better nation's development, Indonesia's economy is also improving. The object of this research is PT. Pegadaian (Persero) Malalayang branch. The purpose of this study is to repair internal goods pawn insurance at PT. Pegadaian (Persero) Malalayang branch. The method used in this research is descriptive method, with data used by internal way of company in pawn collateral goods and draw conclusion. The results of the research can be known about the existing mortgage collateral at PT. Pegadaian (Persero) Malalayang branch is in accordance with the existing theory. The internal control of pawn warranty goods applied by PT Pegadaian Malalayang branch already has a good and efficient system and meet the elements of internal control so that it can improve company performance.Keywords: Internal Control, Mortgage Guarantees